A new species of Eustigmaeus (Acari: Prostigmata: Stigmaeidae) from Vietnam - Alexander A. Khaustov; Sergey M. Tsurikov (Persian Journal of Acarology)
A new species of the genus Eustigmaeus (Acari: Stigmaeidae), E. vietnamiensis sp. nov. is described from the bark of fig tree (Ficus sp.) in Cat Tien National Park, Vietnam. The mite family Stigmaeidae is recorded from Vietnam for the first time.